Youth offline political participation: trends and role of social media - Bahtiar Mohamad,; Abdu Dauda, Shamsu; Haslina Halim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Recently, the growing body of research has waded into the decline of formal political participation and engagement among youth especially voting and party allegiance due to the heightened youth activism such as protests and demonstrations. However, past research proposes that there is a significant relationship between the usage of social media and online political participation among youth. Many of those studies have inordinately relied on college students as samples rather than the entire population of youth with a vast amount of knowledge and experience in. Yet, only few researches have tried to uncover the tendencies of youth participation in formal political activities such as voting and party allegiance via the unprecedented social networking sites such as Facebook to address this issue, the study has employed multiple regression analysis to examine the correlation between use of Facebook, interactivity with politicians, Facebook information quality, political interest and offline political participation among Nigerian youth. This study has shown that Facebook use, interactivity with political figures, Facebook information quality and political interest significantly correlates with offline political participation. Social media allows marginalized youth to interact with friends and political figures, fostering their engagement in political issues, as well as enabling them to share and express their opinions thus draw youth participation in political activities such as voting. Incisively, Facebook serves as a gateway where youth can acquire political knowledge and information. It has become apparent that social media helps to lower the barriers and widen the scope of informal political activities.